The Utility of Routine Postoperative Radiographs After Pinning of Pediatric Supracondylar Humerus Fractures. Issue 5 (July 2017) - Karalius, Vytas P.; Stanfield, Jacob; Ashley, Philip; Lewallen, Laura W.; DeDeugd, Casey M.; Walker, Janet; Larson, Annalise N.; Milbrandt, Todd A.
Abstract : Background: The purpose of this study was to determine the frequency with which postoperative radiographs resulted in a change in management following closed reduction and percutaneous pinning of displaced pediatric supracondylar humerus fractures. We hypothesize that only the initial postoperative radiograph will lead to changes in management of operative supracondylar humerus fractures. Methods: A retrospective review was performed at 2 level I pediatric trauma centers. Inclusion criteria were patients below 18 years of age who sustained supracondylar humerus fractures (Gartland type II, III, IV) who were operatively treated from 2008 to 2013 with adequate radiographic follow-up. Patients with flexion type, intra-articular, transphyseal, and open fractures were excluded from the study. Routine radiographs were taken at initial follow-up (1 wk postoperatively) and at pin removal (3 to 4 wk postoperatively). Results: The final analysis included 572 patients. Initial postoperative radiographs changed treatment in 9 patients (1.6%), including revision surgeries, 2 pin adjustments, and 2 early pin removals. At the time of pin removal, 20 (3.5%) patients required further immobilization. There were no changes to the initial plan for continued nonoperative treatment at final follow-up (6 to 8 wk postoperatively). Conclusions: In this large retrospective series of patients treated with closed reduction and percutaneous pinning of displaced supracondylar humerus fractures, radiographs at 3 weeks do not reveal a need to return to the operating room or other significant pathology. These findings suggest that radiographs should be obtained within 7 to 10 days postoperatively for type III fractures and may only need to be repeated if the clinical situation warrants it, such as severe fracture pattern, persistent pain, or clinical deformity. Level of Evidence: Level IV—case series.